Analisis Penamaan Jalan dan Nilai Historis di Kota Tasikmalaya - Indri Apriliani Jatnika; Milna Widya; Chica Chaswati; Wapa Kamilatul Huda; Aveny Septi Astriani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This research aims to find out the meaning of the names of streets in Tasikmalaya City and analyze the historical value of these street names. This research uses descriptive research methods and uses library study data collection techniques and documentation techniques. Based on the results of the analysis, there are 30 street name data that have similarities in naming patterns. Apart from that, there are 10 analyzes of the meaning and significance of these roads, including meaning nature, meaning plants, animal names, meaning islands, meaning mountains, meaning deep, meaning organizations, meaning buildings, meaning souvenirs, and finally meaning heroes. This research also analyzes the historical value contained in several street names in Tasikmalaya City, such as Jl. SL. Tobing, Jl. Ir. H. Djuanda, Jl. K.H. Zainal Mustofa, etc.